Integration Of Digital Literacy And Language Learning Through Ai Applications For Elementary School Teachers - Winanda Santi Hutami; Veronika Pratiwi; Farida Nugrahani Nugrahani; Benedictus Sudiyana; Nurnaningsih; Wahyu Dini Septiari (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2026)
Abstrak: Kebutuhan literasi digital di kalangan guru dan siswa sekolah dasar saat ini semakin mendesak, seiring berkembangnya teknologi dan perubahan metode pembelajaran. Literasi digital tidak lagi sekadar kemampuan menggunakan perangkat, tetapi bagaimana teknologi dimanfaatkan secara bermakna dalam pembelajaran bahasa. Penguatan literasi digital di SD memungkinkan guru dan siswa mengolah materi sulit menjadi lebih mudah dipahami. Studi empiris oleh Nurhidayah & Wibowo [2] menunjukkan bahwa penggunaan bahan ajar berbasis digital seperti e-book cerita rakyat memberi dampak positif seperti siswa memperoleh pengalaman belajar baru dan bahkan siswa tanpa ponsel dapat ikut mengakses materi digital melalui sekolah. AI dapat meningkatkan kualitas pembelajaran di SD melalui personalisasi materi, evaluasi otomatis, dan pengembangan keterampilan abad ke-21 pada siswa. Melalui PKM literasi digital, pelatihan pemanfaatan AI dalam pembelajaran bahasa, dan pendampingan implementatif guru tidak hanya dibekali kemampuan teknis, tetapi juga pedagogis untuk menciptakan materi ajar adaptif, menarik, dan sesuai kebutuhan siswa. Kata Kunci: Literasi Digital; Pembelajaran Bahasa; Kecerdasan Buatan (AI) Abstract: The demand for digital literacy among elementary school teachers and students is becoming increasingly critical, reflecting technological advancements and evolving learning methods. Digital literacy now encompasses more than just the ability to operate devices; it involves the meaningful application of technology in language education. By enhancing digital literacy in elementary schools, teachers and students can engage with challenging material in more accessible ways. An empirical study by Nurhidayah & Wibowo highlights that the integration of digital teaching resources, such as e-books featuring folk tales, positively influences student learning experiences. Notably, even those students without smartphones can access these digital materials through their schools. Artificial intelligence can further elevate the quality of learning in elementary education by facilitating personalized material, enabling automatic assessments, and fostering essential 21st-century skills in students. Through digital literacy training, the use of AI in language instruction, and supportive mentoring, teachers gain not only the technical competencies but also the pedagogical expertise required to develop adaptive, engaging, and student-centered educational materials. Keywords: Digital Literacy; Language Learning; Artificial Intelligence (AI)